Testing of Solar Powered Adsorption Refrigeration Machine With Collector Area 1m2 Collector Angle 0o - Efsartua Butarbutar (International Journal of Mechanical Computational and Manufacturing Research, 2021)
The sun is one of potential renewable energy resources. One of the utilization of solar energy as the main source of energy for the adsorption refrigeration cycle cooling machine to produce cooling effect. In this research, the type of collector used is flat plate collector. Collector insulation on refrigeration machine use plywood, EVA foam, styrofoam, rockwool, and glass. The surface area of collector is 1 m2 with thick of the plate is 1 mm. In this reasearch carbon active used is technical carbon active/granular filled in collectors as much as 18,5 kg,methanol used is pro-analysis with purity 99,9% as much as 5 liters, and water as cooling medium as much as 6 liters. Tilt angle of collector in this reasearch is 0o. From this reasearch obtained lowest temperature of water is 9,98 oC. Highest total energy absorbed by collector as much as 3,186 MJ with ambient temperature about 28,6 oC